THE PROBLEM OF CHILDREN'S RIGHTS IN CIBURIAL VILLAGE, INDONESIA - Teta Riasih (Politeknik Kesejahteraan Sosial Bandung, 2020)
Children in Ciburial Village experience several problems including discrimination, violence, exploitation, and neglect of children. UU no. 4 of 1979 concerning Child Welfare and Law No. 23 of 2002 in Indonesia concerning Child Protection, states the importance of child protection by parents and the community, but this has not been fully met at the level of implementation. To realize child protection, the Bandung regency government, since 2014 has launched a pioneering child-friendly district by forming a child-friendly village including Ciburial Village, Cimenyan Sub-district. The research approach used was qualitative (field research), the source of data in the research amounted to eight people. The main source is the Ciburial Village leader and several Village officials who determine various village policies and programs that support child protection. Data collection techniques used primarily were group interviews with officials in the village of Ciburial, in addition to that also used in-depth interview techniques. The results showed that the fulfillment of children's rights in the context of supporting a village worthy of children is very good, namely by the availability of social institutions in each of the Five Pillars that guarantee the fulfillment of children's rights, fulfillment of civil rights and freedom of children, the right to health and basic welfare, the availability of the family and care environment alternative for children, the right to education, the use of free time and cultural activities based on local wisdom, and provide special protection. Suggestions in this research are the need to continue to promote socialization on child protection, as well as the provision of human resources who are concerned about the protection of children who come from internal circles of Ciburial Village beside the government officials of Ciburial Village to better coordinate with the Government of Bandung Regency and other agencies so that the fulfillment of children's rights in Ciburial Village can run optimally.